ANALISIS BIAS GENDER DAN DISFEMIA DALAM MEDIA MASSA SEBAGAI BAHAN AJAR MENULIS BERITA - Adriansyah Kusuma Wardani; Any Budiarti (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
Abstract The objective of this study was to reveal the form, type, and function of dysphemia and the manifestation of gender bias in online news texts published by mass media. This study based on the theory of dysphemia by Warren (1992) and Allan & Burridge (2009), as well as the theory of gender injustice by Mansour Fakih (2007). The method used in this study was descriptive qualitative approach with content analysis as its technique. The data were taken from SindoNews online news in the period of December 2024 which relevant to the issue of women and gender violence. The results showed that there were various forms of dysphemia such as taboo words, vulgar expressions, to nicknames, and ridicule used in the context of women's news. Many of the dysphemia in this study functioned to emphasize extreme conditions, humiliate, and characterize certain social groups. In addition, forms of gender bias such as subordination, stereotyping, and marginalization were also found. Based on these findings, researchers developed teaching materials for writing news texts for Phase F that are oriented towards critical literacy and news writing in accordance with journalistic ethics. The results of validation by experts showed that the teaching materials were suitable for use with minor revisions. This research contributes to the development of social issue-based learning and gender sensitivity in Indonesian language education.